Degree of Polymer Organization Decreases the Binding of a Monoclonal Antibody Raised against the β-Chain Amino Terminus of Fibrin - Morris, Timothy A; Marsh, James J; Fagnani, Roberto; Hagan, Michael; Moser, Kenneth M (Thrombosis and Haemostasis, 1997)
Accurate non-invasive diagnosis of deep venous thrombosis and pulmonary embolism remains an elusive goal. Radiolabeled antibodies specific for the epitope exposed on the β-chain of fibrin after fibrino- peptide B release (anti-β) enabled in situ imaging of thrombi in experimental subjects with nuclear medicine techniques. When used in patients anticoagulated for thrombo-embolic disease, however, the antibody was unable to reliably image the thrombi. We postulated that the neoepitope on the β-chain of fibrin is covered up as fibrin organizes into a polymer network and is therefore exposed to the antibody only during active incorporation of fibrin subunits. We determined the equilibrium binding kinetics of an anti-β monoclonal antibody to fibrin in various stages of organization. The concentration of exposed epitopes on immobilized fibrin monomers was equal to the molar concentration of fibrin β-chains. The percentage of β-chains exposed to the antibodies markedly decreased as the fibrin network was allowed to organize, a process catalyzed by calcium. Conclusions: The β-chain amino terminus of fibrin is exposed transiently as subunits are added to the enlarging fibrin network. Anti-β antibodies bind preferentially to actively enlarging fibrin polymers.